Are Gastrointestinal Symptoms Important in Patients with COVID-19? - Büküm, Emine; Oğuz Ayarcı, Ayşe; Güler, Kadir (Turkish Journal of Gastroenterology, 2023)
Background: Our study aimed to present the general characteristics of patients in our country with coronavirus disease 2019 (COVID-19) having gastrointestinal system symptoms and the effects of gastrointestinal system symptoms on prognosis in the light of literature. Methods: This retrospective single-center study included patients who tested positive for COVID-19 in polymerase chain reaction test and were treated as symptomatic inpatients between April 1, 2020, and May 15, 2020, at the Bursa City Hospital in Turkey. Results: In our study, 292 patients with positive COVID-19 polymerase chain reaction test and symptoms were included to investigate the effect of gastrointestinal system symptoms in COVID-19 patients. Patients with at least 1 gastrointestinal system symptom were named group 1, and patients with no gastrointestinal system symptoms were named group 2. Compared with group 1 (145 patients), group 2 (147 patients) had patients with significantly older age (P = .010) and significantly higher rates of intensive care unit admission (P = .023), intubation (P = .021), and exitus (P = .004). The white blood cell count (P = .001) and C-reactive protein (P = .001) values were significantly higher in group 2 than in group 1. Conclusion: COVID-19 is primarily a disease with respiratory symptoms, but gastrointestinal system symptoms are also seen. In our study, we found that patients with gastrointestinal system symptoms had a better prognosis. The reason for this may be the early hospitalization of the patients due to gastrointestinal system symptoms and the early initiation of treatment. However, comprehensive studies are still needed to elucidate this further. Cite this article as: Büküm E, Oğuz Ayarcı A, Güler K. Are gastrointestinal symptoms important in patients with COVID-19? Turk J Gastroenterol. 2023;34(3):203-210.